PELATIHAN VIDEO PEMBELAJARAN BAGI INSTRUKTUR SEKOLAH PERHOTELAN BALI DAN GURU SMK DUTA BANGSA - Ni Made Dwi Wulan setyawati -; I Wayan Eka Sudarmawan; Made Arya Astina (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
This article presents the results of community service activities conducted by the authors' team due to the need for digital-based learning media to respond to the learning needs of Gen Z students. This activity aims to enhance the competencies of instructors and teacher in creating educational videos using the CapCut application. The activity was held at Bali Film School and attended by 15 participants from Bali Hospitality School and SMK Duta Bangsa. The workshop covered content planning, filming techniques, and video editing processes. Evaluations through questionnaires indicated that most participants were very knowledgeable or knowledgeable in using CapCut, although some specific features still required further explanation. The workshop results showed an improvement in participants' skills in utilizing digital technology for education. This activity is expected to support digital transformation in the education sector and improve teaching quality.